Peran Cs (Customer Service) Dalam Menangani Keluhan Nasabah Pada Bank Nagari Cabang Utama Padang - Asyahta, Salsabila; Edlina, Ria (CV. ITTC INDONESIA, 2024)
Customers who make complaints regarding ATM cards can be resolved directly by customer service at that time, however complaints about electronic biller transactions must be reported first to the head office, customers are asked to wait a few days. Customers who make complaints but feel they are not being provided with service rights cause disappointment with the company for the community. This research uses qualitative methods. Qualitative research is research conducted comprehensively on an object. Then the research results are explained in the form of words obtained through valid data. Customer service plays the role of receiving complaints and then providing solutions according to the problems the customers complain about. There are 5 indicators of service quality according to Parasuraman, Zeithaml and Berry, namely: tangibility, reliability, responsiveness, empathy and assurance. From a series of interviews, it was found that customer service was less responsive in responding to electronic biller transaction complaints. So the author suggests to the CS of Bank Nagari Main Branch to be more responsive in terms of service quality indicators